Formulasi susu berkhasiat anti flu burung dan anti diare; produksi imunoglobulin Y dalam berbagai bentuk - Rahmat Hidayat; Fachriyan Hasmi Pasaribu (Institut Pertanian Bogor, 2010)
The ultimate goal of fresh milk formulations are efficacious against-bird flu and diarrhea (against Escherichia coli and Salmonella enteritidis). Outputs generated in this first year of immunoglobulin Y anti-bird flu and anti-diarrhea in various forms of spray dry yolk, dry freeze egg yolks, and pure extracts. lg Y that collected is located in the egg yolks and tested positive for HSNl virus, E. coli and S. enteritidis. Production of Ig Y begins with the treatment in the form of vaccination in laying hens 4 (four) times during the 4 (four) weeks. The vaccines were used in the form of HSNl in the first and third week, while E. coli and S. enteritidis used every week. Serum and yolk was collected and checked for the presence of anti-lg Y was the third agent since the first week after the last vaccination. Inspection method for E. coli and S. Enteritidis is the order Presipitation Gel Test (AGPT) while the HSNl method Haemagglutination Inhibition (HI). The results give a positive result against all three antigens, but in a different week. This situation is common given the immunity of each chicken is different depending on race, age and environment.